Form four chemistry teachers’ conceptualization of pedagogical content knowledge / Chien Lee Shing - Chien, Lee Shing (2016)

(untitled)
Pedagogical content knowledge (PCK) was defined as the knowledge of teaching resulted from the integration of pedagogy and subject matter knowledge. This study looked into the conceptualization of pedagogical content knowledge and the teaching processes of the four Form Four Chemistry teachers while teaching topic 3 ‘Chemical Formulae and Equations’ in the Form 4 Chemistry curriculum. The four Chemistry teachers were chosen from various schools based on their given consent and availability for observations. The methods of data collection consisted of classroom observations, interviews, field notes, and documentation. The classroom observations were conducted on all the lessons taught in topic 3. Both the interviews and classroom observations were audibly recorded and transcribed. Coding was done on the data to form sub themes which were later collapsed into themes. The coding of the data was guided by the research questions and new themes were allowed to emerge from the data. The data collected from various sources were triangulated with each other. The findings of this study showed that: (i) the chemistry teachers perceived content knowledge, pedagogical skills and student as essential components of their teaching; (ii) the PCK attributes of the chemistry teachers developed and grew with their teaching experience but at different rates; (iii) the teaching processes of the teachers were mostly similar to those in the PRA model; and (iv) the teachers lacked a few aspects such as assessment on students’ conceptual understanding and own teaching, student knowledge and new comprehension. As a whole, the teaching of the four Form Four chemistry teachers was teacher-oriented, algorithmic, using chalk-and-talk approach which did not support thoughtful and meaningful and optimal learning among the students. A framework of collaboration was iii proposed to help the chemistry teachers develop and expand their PCK evenly and holistically. At the same time, a few topic specific PCK which can be used as training materials in the professional training program for pre-service and in-service Chemistry teachers were identified.